Outcome of Fetuses with Anterior Abdominal Wall Defects in A Tertiary Referral Hospital - Alifa, Dhara; Aziz, Muhammad Alamsyah; Ritonga, Mulyanusa Amarullah; Pribadi, Adhi (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: The most common abdominal wall defects are gastroschisis and omphalocele. Gastroschisis is a case of intraabdominal herniation caused by an abdominal wall defect from exposure to amniotic fluid during pregnancy. Omphalocele is a case of intraabdominal herniation covered with a membranous sac on the umbilical cord’s base. Gastroschisis occurred in 1/4000 of the of the global birth rate. Prevalence of omphalocele in between 1/3000 and 1/5000 cases of pregnancy. The purpose of the purpose of the research  is to present an overview of patients with congenital defects such as Gastroschisis and Omphalocele.Method: Research design is observational and descriptive. Data obtained from medical records in Hasan Sadikin tertiary referral hospital Bandung. Sample size was obtained by total sampling and conducted in April 2020–April 2023. Results: The demographics of gastroschisis include male (50%), female (50%), preterm (20%), stillbirth (30%), severe asphyxia (14.29%), moderate asphyxia (57.14%), normal asphyxia (8.57%), newborn mortality (14.29%), and other congenital anomalies (40%). In comparison, the demographics of omphalocele are male (66.67%), female (33.33%), preterm (58.33%), stillbirth (16.67%), severe asphyxia (40%), moderate asphyxia (40%), normal asphyxia (20%), newborn mortality (50%), and other congenital abnormalities (25%). Abdominal wall defects are seldom related with gender.Conclusion: Abdominal wall defect is a very rare congenital abnormality. This abnormality will require primary abdomen closure surgery to enhance the baby’s prognosis. The more other risk factors exist within abdominal wall defect babies, the worse their following prognosis will be. The prognosis for omphalocele is more severe than gastroschisis due to the presence of asphyxia and prematurity.Luaran Janin dengan Defek Dinding Abdominal Anterior di Rumah Sakit Rujukan TersierAbstrakPendahuluan: Cacat dinding depan abdomen yang paling banyak terjadi adalah gastroschisis dan omphalocele. Gastroschisis adalah kasus herniasi intraabdomen yang disebabkan oleh cacat dinding perut akibat paparan cairan ketuban selama kehamilan. Omphalocele adalah kasus herniasi intraabdomen yang ditutupi kantung membran di dasar tali pusat. Gastroschisis terjadi pada 1/4000 angka kelahiran global. Prevalensi omfalokel antara 1/3000 dan 1/5000 kasus kehamilan. Tujuan dari penelitian ini adalah untuk menyajikan gambaran pasien dengan kelainan bawaan seperti Gastroschisis dan Omphalocele.Metode: Desain penelitian adalah observasional dan deskriptif. Data diperoleh dari rekam medis di rumah sakit rujukan tersier Hasan Sadikin Bandung. Besar sampel diperoleh dengan cara total sampling dan dilakukan pada bulan April 2020–April 2023.Hasil: Demografi gastroschisis meliputi laki-laki (50%), perempuan (50%), prematur (20%), lahir mati (30%), asfiksia berat (14,29%), asfiksia sedang (57,14%), asfiksia normal (8,57%). ), kematian bayi baru lahir (14,29%), dan kelainan kongenital lainnya (40%). Sebagai perbandingan, demografi omfalokel adalah laki-laki (66,67%), perempuan (33,33%), prematur (58,33%), lahir mati (16,67%), asfiksia berat (40%), asfiksia sedang (40%), asfiksia normal (20). %), kematian bayi baru lahir (50%), dan kelainan bawaan lainnya (25%). Cacat dinding perut jarang berhubungan dengan jenis kelamin.Kesimpulan: Cacat dinding perut merupakan kelainan bawaan yang sangat tidak biasa. Kelainan ini memerlukan operasi penutupan perut utama untuk meningkatkan peluang hidup bayi. Adanya faktor risiko tambahan pada bayi baru lahir dengan kelainan dinding perut memperburuk prognosisnya. Omphalocele sering menyebabkan asfiksia dan prematur, sehingga prognosisnya lebih buruk dibandingkan gastroschisis.Kata Kunci : Cacat dinding depan abdomen, Gastroschisis, Omphalocele